Type designations for fireflies (Coleoptera: Lampyridae) of the Biologia Centrali Americana Gorham, 1881 housed in the Natural History Museum, London - Martin, Gavin J.; Powell, Gareth S. (Zootaxa, 2020)
The Biologia Centrali Americana (B.C.A.) is comprised of eight volumes that deal specifically with Coleoptera. These volumes were split into 18 parts and were published between 1879 and 1911. The family Lampyridae was treated in two parts, the main text (1881) with a supplement (1884). Within volume three, part 2, Gorham lists ~90 species in 14 genera, not including the Phengodini subfamily. Of these, Gorham provided original descriptions for 37 species. During recent research visits (2018 and 2020) the authors were able to study material pertinent to the B.C.A. We were able to confidently designate holotypes, lectotypes, and paralectotypes following ICZN articles 73.1 and 74.1 within these species. Two species described by Gorham (1881) are not treated here. Phaenolis nirgricollis was located with a single specimen, already designate as the holotype. Two female syntypes of Photinus consanguineous were located, however Oliver (1907) synonymized these females with Photinus pyralis. These designations contribute to a larger taxonomic effort to stabilize the nomenclature of this group. The species described in the supplement will be treated in a future work. Subfamilies are listed according to Martin et al. (2019) and genera/species within each subfamily are listed according to the order in Gorham (1881).